2013
DOI: 10.1111/clr.12179
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Implant transmucosal design on early peri‐implant tissue responses in beagle dogs

Abstract: Concave-machined profiled implants with a transmucosal design may induce less bone resorption and better connective tissue attachment around implants than the straight-machined profiled implants during the early healing phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Kim et al 14 reported no difference in soft tissue vertical values on concave, straight, or flared transmucosal profiles after 6 months of unloaded healing, with the following values of 2.72 (straight), 2.91 (narrow), and 3.04 mm (flared). However, Huh et al 15 reported lower periimplant mucosa heights on concave transmucosal profiles (2.36 mm) compared to straight transmucosal profiles (2.88 mm) after 16 weeks of healing, but the results were not statistically significant. These propensities are in accordance with the present findings.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Kim et al 14 reported no difference in soft tissue vertical values on concave, straight, or flared transmucosal profiles after 6 months of unloaded healing, with the following values of 2.72 (straight), 2.91 (narrow), and 3.04 mm (flared). However, Huh et al 15 reported lower periimplant mucosa heights on concave transmucosal profiles (2.36 mm) compared to straight transmucosal profiles (2.88 mm) after 16 weeks of healing, but the results were not statistically significant. These propensities are in accordance with the present findings.…”
Section: Discussionmentioning
confidence: 94%
“…However, controversial outcomes were reported about periimplant mucosa dimensions. According to Kim et al, 14 the vertical dimensions of the periimplant mucosa were similar on concave, straight, or flared transmucosal 1-piece implants after 6 months of unloaded healing in the beagle dog, whereas Huh et al 15 reported that a concave transmucosal design led to lower biological width vertical values compared to straight profiles after 16 weeks of loaded healing in the beagle dog.…”
mentioning
confidence: 98%
“…While some experimental studies find reduced buccal crestal bone loss around implants applying the concept of platform shift/switch, others observe extensive buccal crestal bone loss and consequently limited benefit with the platform shift/switch approach . A related concept is the development of concave abutments or implant necks to support/stabilize the mucosal profile – for particular use in the anterior maxilla and, interestingly, also used to enhance the dermal adherence of bone‐anchored hearing aids . Nevertheless, a systematic review concerning the efficacy of scalloped or platform shift/switch implants and gingivally converging or concave implant abutments concludes, “The current literature provides insufficient evidence about the effectiveness of different implant abutment designs and materials in the stability of peri‐implant tissues,” justifying additional evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of responding program directors reported instructing residents to design provisional implant restorations with either a straight/linear or concave emergence morphology, with less than 10% advocating a convex morphology. Such instructional preferences and trends may also be attributable to emerging evidence of a relationship between the abutment transition zone morphology and peri-implant mucosal outcomes, [27][28][29][30][31] although such clarifying questions were not posed in our survey. The majority of the graduate periodontics program directors in our study also reported advising their residents to maintain patients in provisional implant restorations for a minimum of one to three months, with greater than half maintaining patients with provisional restorations for greater than three months.…”
Section: Discussionmentioning
confidence: 99%